THE LEARNING MODEL IMPLEMENTATION OF SASAK, BALI-LOMBOK AND BUGIS ETHNICITY MULTIGENIC-HOMOGENIC LOCAL TRADITION-BASED CIVICS LITERACY IN MATARAM CITY ELEMENTARY SCHOOL LOMBOK WEST NUSATENGGARA - Solihin Ichas Hamid; Tuti Istianti; Baiq Zohri Uyni; Ni Nyoman Elly Setiawati; G. Ayu Ariyanthi (International Journal of Social Science, 2021)
The implementation of collaboration with teachers in SDN Selaprang 7 and Cakranegara 1 Mataram City Lombok NTB was conducted corresponding to health protocol during the pandemic situation, that is, the by the dual system, both using technological information devices teachers visit program to student’s group. Apart from the situational limitation, the ethnic-pedagogic approach in this research delivers a visible outcome target, at least in the behavior changes and teachers' understanding of the demand of multidimensional Literacy development, which is a part of the curriculum message content for building student's character since elementary school. Exploring the local wisdom value contained in a variety of traditional arts such as verbal expressions, audial chants, visual appearances, and combinations of games and exhibitions, either virtual or directly, has the potential to become a medium is the message in cultural literacy and citizenship development. Traces marks and learning outcomes of citizenship literacy models based on homogeneous and multigenic local wisdom in elementary schools of Mataram City, Lombok, NTB found in this study are : 1) teachers’ involved research collaboration for developing Civics Literacy in elementary school can make integral revitalization of their professional task demand to encourage the process and learning outcome of the students’ entirely conforming to the elementary school students’ requirements; 2) Covid-19 pandemic situation, aside as an obstacle for achieving learning standard, remain gives the opportunity to develop technological network-based learning alternative with its all practical innovation and combination in the field; 3 the implementation of Civics Literacy development becomes pleasant refreshment medium for student from monotone situation as a result of partial academic assignments because it integrates learning activities in which it will more explore students’ potential in absorbing and internalizing cultural values instilled within family and community both homogeneously and multi-culturally.